Efektivitas Media Video SADARI Terhadap Praktik SADARI pada Remaja Putri di SMK PGRI Sampit - Herlinadiyaningsih Herlinadiyaningsih; Heti Ira Ayue (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Breast Self-Examination (BSE) is a breast self-examination that is carried out to find an abnormal lump in the breast or detect breast cancer early, especially among young women who have not been exposed to information about BSE, especially among young women at SMK PGRI Sampit. This research aims to convey information and education among adolescents who have not been exposed to learning and knowledge about BSE, especially at SMK PGRI Sampit. The type of research used in this research is quasi-experimental research, with a